Positive electrode active material, positive electrode, and rechargeable lithium battery

CN122992012APending Publication Date: 2026-10-27SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610526322.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-25
Filing Date
2026-04-21
Publication Date
2026-10-27

Smart Images

  • Figure CN122992012A_ABST
    Figure CN122992012A_ABST
Patent Text Reader

Abstract

Some example embodiments provide a positive electrode active material, a positive electrode including the same, and a rechargeable lithium battery. The positive electrode active material includes: core particles in the form of secondary particles in which a plurality of primary particles are agglomerated, including a lithium-nickel-based composite oxide; and a coating layer provided on a surface of the core particles and containing cobalt, aluminum, and yttrium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] A positive electrode active material, a positive electrode including the positive electrode active material, and a rechargeable lithium battery are disclosed. Background Technology

[0002] Portable information devices such as cellular phones, laptops, and smartphones use rechargeable lithium batteries, which have high energy density and are easy to carry, as their power source. High-energy-density rechargeable lithium batteries are also used as driving power sources or energy storage sources in hybrid or electric vehicles.

[0003] Various positive electrode active materials are already used in rechargeable lithium batteries. With the recent rapid increase in demand for large-size, high-capacity, or high-energy-density rechargeable lithium batteries, there is a need to develop positive electrode active materials that can increase capacity while ensuring stability and enabling operation at high voltages. Summary of the Invention

[0004] Positive electrode active materials, positive electrodes, and rechargeable lithium batteries comprising lithium nickel-based composite oxides are provided, which have a coating layer that improves capacity characteristics, initial charge / discharge efficiency, high-temperature storage characteristics, and high-temperature cycle life characteristics.

[0005] In some embodiments, the positive electrode active material includes: a core particle in the form of an agglomeration of secondary particles as primary particles, comprising a lithium nickel-based composite oxide; and a coating layer disposed on the surface of the core particle and containing cobalt, aluminum and yttrium.

[0006] In some example embodiments, the positive electrode includes a current collector; and a layer of positive electrode active material on the current collector; wherein the layer of positive electrode active material includes the aforementioned positive electrode active material.

[0007] In some example implementations, the rechargeable lithium battery includes: the positive electrode; the negative electrode; and the electrolyte.

[0008] Positive electrode active materials according to some exemplary embodiments and rechargeable lithium batteries using said positive electrode active materials can exhibit low resistance, high initial charge / discharge capacity and efficiency, excellent high-temperature storage characteristics and high-temperature cycle life characteristics, and long cycle life characteristics. Attached Figure Description

[0009] Figure 1 This is a diagram of a cylindrical rechargeable lithium battery.

[0010] Figure 2 This is a cross-sectional view of a prismatic rechargeable lithium battery.

[0011] Figure 3 and 4A schematic exploded perspective view of a pouch-type rechargeable lithium battery.

[0012] Figure 5 This is an SEM image of the surface of the positive electrode active material prepared in Example 2.

[0013] Figure 6 This is a SEM image of the surface of the positive electrode active material prepared in Comparative Example 1.

[0014] Figure 7 This is a SEM image of the surface of the positive electrode active material prepared in Comparative Example 4.

[0015] Figure 8 This is a SEM image of the surface of the positive electrode active material prepared in Comparative Example 6.

[0016] Figure 9 This is a SEM-EDS image of yttrium in the coating layer on the surface of the positive electrode active material prepared in Example 2.

[0017] Figure 10 This is a SEM-EDS image of yttrium in the coating layer in the cross-section of the positive electrode active material prepared in Example 2. Detailed Implementation

[0018] Specific embodiments are described in detail below to enable those skilled in the art to readily implement them. However, this disclosure may be embodied in many different forms and is not to be construed as limited to the embodiments set forth herein.

[0019] The terminology used herein is for descriptive purposes only and is not intended to limit the scope of this disclosure. Unless the context clearly specifies otherwise, singular expressions include plural expressions.

[0020] As used in this article, “combination of” means mixtures, laminates, complexes, copolymers, alloys, blends, reaction products, etc. of the constituent elements.

[0021] Terms such as “comprising,” “including,” or “having” are intended to indicate the presence of the features, quantities, steps, elements, or combinations thereof embodied, but do not preclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or combinations thereof.

[0022] In the accompanying drawings, for clarity, the thickness of layers, films, panels, regions, etc., may be exaggerated, and the same reference numerals denote the same elements throughout the specification. It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it may be directly on said other element, or there may be intermediate elements present. Conversely, when an element is referred to as being "directly on" another element, there are no intermediate elements present.

[0023] The term "layer" in this article includes not only shapes that form across the entire surface when viewed from a plan view, but also shapes that form on a portion of the surface.

[0024] The average particle size can be measured by methods known to those skilled in the art, such as by a particle size analyzer or by transmission electron microscopy or scanning electron microscopy images. Alternatively, the average particle size value can be obtained by measuring using dynamic light scattering, performing data analysis, counting the number of particles in each particle size range, and calculating the average particle size therefrom. As used herein, unless otherwise defined, the average particle size means the diameter (D) of the particles having a cumulative volume of 50% of the particle size in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of approximately 20 particles in a scanning electron microscopy image. 50 ).

[0025] "Or" is not interpreted as having an exclusive meaning. For example, "A or B" is interpreted as including A, B, A+B, etc.

[0026] "Metals" include common metals, transition metals, and metalloids (semi-metals).

[0027] Positive electrode active material

[0028] In some embodiments, the positive electrode active material includes: a core particle in the form of an agglomeration of secondary particles as primary particles, comprising a lithium nickel-based composite oxide; and a coating layer disposed on the surface of the core particle, wherein the coating layer comprises cobalt, aluminum and yttrium.

[0029] In some embodiments, a coating layer comprising cobalt, aluminum, and yttrium on the surface of the core particle improves high-temperature cycle life characteristics, high-temperature storage characteristics, and initial charge / discharge efficiency by introducing a coating layer containing cobalt, aluminum, and yttrium. The coating layer strengthens the particle surface and forms 3D lithium channels in the structure.

[0030] Core Particles

[0031] According to some embodiments, the core particles comprise a lithium-nickel-based composite oxide represented by chemical formula 1.

[0032] [Chemical Formula 1]

[0033] Li a1 Ni x1 M 1 y1 M 2 z1 O 2-b1 X b1

[0034] In Chemical Formula 1, 0.9≤a1≤1.8, 0.3≤x1≤1, 0≤y1≤0.7, 0≤z1≤0.7, 0.9≤x1+y1+z1≤1.1 and 0≤b1≤0.1, M 1 and M 2 are different from each other and each is one or more of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr, and X is one or more of F, P and S. In further embodiments relating to Chemical Formula 1, 0.6≤x1≤1, 0≤y1≤0.4, and 0≤z1≤0.4, or 0.8≤x1≤1, 0≤y1≤0.2, and 0≤z1≤0.2, or 0.9≤x1<1, 0<y1≤0.1, and 0≤z1≤0.1.

[0035] As a specific example, the lithium-nickel based composite oxide may be represented by Chemical Formula 2 or Chemical Formula 3.

[0036] [Chemical Formula 2]

[0037] Li a2 Ni x2 Co y2 M 3 z2 O 2-b2 X b2

[0038] In Chemical Formula 2, 0.9≤a2≤1.2, 0.8≤x2<1, 0<y2≤0.2, 0≤z2≤0.2, 0.9≤x2+y2+z2≤1.1 and 0≤b2≤0.1, M 3 is one or more of Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr, and X is one or more of F, P and S. In further embodiments relating to Chemical Formula 2, 0.9≤x2≤0.99, 0.01≤y2≤0.1, and 0≤z2≤0.1.

[0039] [Chemical Formula 3]

[0040] Li a3 Ni x3 Coy3 M 4 z3 M 5 w3 O 2-b3 X b3

[0041] In chemical formula 3, 0.9 ≤ a³ ≤ 1.2, 0.8 ≤ x³ ≤ 0.98, 0.01 ≤ y³ ≤ 0.19, 0.01 ≤ z³ ≤ 0.19, 0 ≤ w³ ≤ 0.19, 0.9 ≤ x³ + y³ + z³ + w³ ≤ 1.1 and 0 ≤ b³ ≤ 0.1, M 4 It is one or more of Al and Mn, M 5 X is one or more of B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn, and Zr, and X is one or more of F, P, and S. In a further embodiment of chemical formula 3, 0.9 ≤ x³ ≤ 0.98, 0.01 ≤ y³ ≤ 0.09, 0.01 ≤ z³ ≤ 0.09, and 0 ≤ w³ ≤ 0.09.

[0042] Lithium-nickel-based composite oxides can be high-nickel-based positive electrode active materials having a nickel content of greater than or equal to about 80 mol%, for example greater than or equal to about 82 mol%, greater than or equal to about 85 mol%, greater than or equal to about 87 mol%, greater than or equal to about 90 mol%, or greater than or equal to about 91 mol% and less than or equal to about 99 mol%, for example less than or equal to about 95 mol%, based on 100 mol% of total metals other than lithium. High-nickel-based positive electrode active materials can be used to provide high-capacity, high-density rechargeable lithium batteries.

[0043] In lithium-nickel-based composite oxides, based on 100 mol% of total metals excluding lithium, the cobalt content can be greater than or equal to about 1 mol%, for example, about 1 mol% to about 10 mol%, about 1 mol% to about 5 mol%, or about 1 mol% to about 3 mol%. When the cobalt content is within these ranges, it effectively suppresses particle damage during the compression process, prevents accelerated particle degradation during charging and discharging, and establishes a kinetic balance between lithium ions and electrons, which has the advantage of improving the cycle life characteristics of rechargeable lithium batteries.

[0044] The lithium-nickel-based composite oxide can be, for example, a lithium-nickel-cobalt-aluminum-based composite oxide that further includes aluminum in addition to nickel and cobalt. When aluminum is included in the lithium-nickel-based composite oxide, a stable layered structure can be advantageously maintained even when a small amount of cobalt is included. The amount of aluminum, based on 100 mol% of the total metals other than lithium in the lithium-nickel-based composite oxide, can be greater than or equal to about 0.1 mol%, greater than or equal to about 0.5 mol%, or greater than or equal to about 1 mol%, for example, about 1 mol% to about 3 mol%, about 1 mol% to about 2.5 mol%, or about 1 mol% to about 2 mol%. Here, the amount of aluminum refers to the content of aluminum present in the core particles. When the aluminum content is within these ranges, a stable structure can be maintained even when a small amount of cobalt is included in the core particles, structural collapse due to charging and discharging can be suppressed, and long cycle life characteristics of the positive electrode active material can be achieved.

[0045] The core particle can be in the form of a secondary particle, which is an agglomeration of primary particles. The secondary particles can be spherical, ellipsoidal, polyhedral, irregular in shape, or a combination thereof, and the primary particles can be spherical, ellipsoidal, plate-like, or a combination thereof.

[0046] Under high-temperature conditions, core particles can be easily chemically corroded by the components of the electrolyte. This leads to frequent side reactions with the electrolyte, resulting in reduced cycle life and safety. However, these problems can be addressed by introducing a coating layer as described in the embodiments below.

[0047] Coating layer

[0048] According to some embodiments, the positive electrode active material includes a coating layer disposed on the surface of the core particle, wherein the coating layer includes cobalt, aluminum and yttrium.

[0049] In the positive electrode active material, based on 100 mol% of total metals excluding lithium, the amount of cobalt in the coating layer can be from about 0.1 mol% to about 5.0 mol%, for example from about 0.5 mol% to about 4.0 mol%, from about 1.0 mol% to about 3.0 mol%, or from about 1.5 mol% to about 2.5 mol%. The cobalt content refers only to the amount of cobalt contained in the coating layer, regardless of the cobalt included in the core particles.

[0050] In the positive electrode active material, based on 100 mol% of total metals excluding lithium, the amount of aluminum in the coating layer can be from about 0.1 mol% to about 3.5 mol%, for example, from about 0.1 mol% to about 3.0 mol%, from about 0.2 mol% to about 2.5 mol%, from about 0.2 mol% to about 2.0 mol%, from about 0.3 mol% to about 1.5 mol%, from about 0.3 mol% to about 1.0 mol%, or from about 0.4 mol% to about 0.7 mol%. The aluminum content of the coating layer refers only to the amount of aluminum included in the coating layer, regardless of the amount of aluminum included in the core particles.

[0051] Additionally, in the positive electrode active material, based on 100 mol% of total metals excluding lithium, the amount of yttrium in the coating layer can be from about 0.1 mol% to about 0.5 mol%, for example, from about 0.1 mol% to about 0.4 mol%, from about 0.1 mol% to about 0.3 mol%, or from about 0.1 mol% to about 0.2 mol%. The yttrium content of the coating layer refers only to the yttrium content included in the coating layer, regardless of the yttrium that may be included in the core particles.

[0052] In the positive electrode active material, based on 100 mol% of total metals excluding lithium, the ratio of cobalt content to aluminum content (Co / Al) can be from about 1.5 to about 2, for example from about 1.6 to about 2. This refers to the content of cobalt and aluminum included in the coating layer and the core particles. When these ratios are met, the initial charge / discharge efficiency, high-temperature storage, and high-temperature cycle life characteristics of rechargeable lithium batteries can be improved.

[0053] The cobalt, aluminum, and yttrium content in the coating layer can be measured, for example, by SEM-EDS (scanning electron microscopy-energy dispersive X-ray spectroscopy) analysis of the surface of the positive electrode active material. When the cobalt, aluminum, and yttrium content in the coating layer is within these ranges, a thin and uniform coating layer can be formed, the resistance of the positive electrode active material does not increase, and side reactions with the electrolyte are effectively suppressed, thereby improving the cycle life and storage characteristics of rechargeable lithium batteries under high-temperature conditions. When the cobalt, aluminum, and yttrium content in the coating layer is too high, a uniform coating layer may not be formed or the resistance may increase, which can lead to reduced charge / discharge efficiency and cycle life characteristics. When the cobalt, aluminum, and yttrium content in the coating layer is too low, a coating layer of appropriate thickness cannot be formed, which can result in less suppression of side reactions with the electrolyte.

[0054] According to some embodiments, the coating layer can be in the form of a film continuously surrounding the surface of the core particle, or it can be in the form of a shell surrounding the entire surface of the core particle. This differs from structures in which only a portion of the surface of the core particle is coated. According to some embodiments, the coating layer can completely cover the surface of the core particle while being formed in a very thin and uniform form, thereby providing the positive electrode active material with improved structural stability without increasing resistance or reducing capacity, effectively suppressing side reactions with the electrolyte, reducing gas generation under high voltage and high temperature conditions, and providing long cycle life characteristics.

[0055] During the formation of the cobalt and aluminum coating, cobalt and aluminum can diffuse into the secondary particles. Therefore, according to some embodiments, the positive electrode active material may further include a grain boundary coating (coating portion), which is located on the surface of the primary particles within the inner portion of the secondary particles and contains cobalt and aluminum. The inner portion of the secondary particles means the entire interior of the secondary particles excluding the surface. For example, the inner portion may mean the entire interior from a depth of approximately 1 μm from the outer surface. The inner portion may also refer to a portion that is inaccessible to distilled water when the secondary particles of the positive electrode active material are washed with distilled water. The grain boundary coating is distinct from the coating layer on the surface of the secondary particles and refers to the coating formed on the surface of the primary particles located within the inner portion of the secondary particles. The presence of the grain boundary coating can be confirmed by SEM-EDS analysis of the cross-section of the positive electrode active material. By forming the cobalt and aluminum grain boundary coating, cobalt and aluminum do not act as resistors and can effectively suppress structural collapse or breakage of the positive electrode active material due to charging and discharging.

[0056] There are no restrictions on the cobalt and aluminum content within the grain boundary coating. For example, the cobalt content within the grain boundary coating can be less than the cobalt content within the coating layer, and the aluminum content within the grain boundary coating can be less than the aluminum content within the coating layer.

[0057] According to some implementation methods, yttrium can exist in the coating layer in the form of islands.

[0058] According to some embodiments, the coating layers may each have a thickness of about 5 nm to about 200 nm, for example, about 5 nm to about 150 nm, about 5 nm to about 100 nm, about 5 nm to about 80 nm, about 5 nm to about 50 nm, or about 10 nm to about 50 nm. If the coating layer is within these thickness ranges, the structural stability of the positive electrode active material can be improved without increasing resistance or reducing capacity due to the coating layer, and side reactions with the electrolyte can be effectively suppressed. The thickness of the coating layer can be measured, for example, by SEM (scanning electron microscopy), TEM (transmission electron microscopy), TOF-SIMS (time-of-flight secondary ion mass spectrometry), XPS (X-ray photoelectron spectroscopy), or EDS (energy dispersive spectroscopy) analysis and, for example, by EDS line profile analysis of the cross-section of the positive electrode active material.

[0059] According to some example embodiments, the coating layers are thin, each having a thickness of tens to hundreds of nanometers, and each being uniform. For example, the deviation in the coating layer thickness within a positive electrode active material particle may be less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15%. Here, the deviation in coating layer thickness refers to the coating layer thickness within a single positive electrode active material particle. The deviation in coating layer thickness can be calculated as follows: the thickness is measured at approximately 10 points in an electron microscope image of a cross-section of a positive electrode active material particle to calculate the arithmetic mean; then, the absolute value of the difference between a thickness data and the arithmetic mean is divided by the arithmetic mean, and then multiplied by 100. When the deviation or standard deviation of the coating layer thickness is within the above range, a coating layer of uniform thickness is formed on the surface of the positive electrode active material particle with a good shape. Therefore, the structural stability of the positive electrode active material is improved, side reactions with the electrolyte are effectively suppressed, and the increase in resistance or decrease in capacity due to coating is minimized.

[0060] In addition to cobalt, aluminum, and yttrium, the coating layer may also contain nickel. Nickel may be included in the core particles and introduced during the coating layer formation process. There is no limitation on the nickel content. According to some embodiments, the coating layer substantially (essentially) contains cobalt, aluminum, and yttrium, and optionally contains nickel, formed to have a thin, uniform thickness. Such a coating layer improves the high-voltage characteristics of the positive electrode active material and enhances the cycle life characteristics of the battery.

[0061] In addition to cobalt, aluminum, and yttrium, the coating may also include sulfur. Sulfur may be introduced during the formation of the coating by introducing aluminum sulfate into the aluminum raw material or cobalt sulfate into the cobalt raw material. There is no particular limitation on the sulfur content. According to some embodiments, the coating substantially (essentially) contains cobalt, aluminum, and yttrium, and optionally contains sulfur. Such a configuration improves the cycle life characteristics of the positive electrode active material.

[0062] The span of the positive electrode active material according to some example embodiments may be about 0.9 to about 1.2, for example about 1.0 to about 1.2, about 0.9 to about 1.1, or about 1.0 to about 1.1. In this case, the span can be calculated using Equation 1 below. When the span of the positive electrode active material is within these ranges, the density of the positive electrode active material layer including the positive electrode active material increases, resulting in high energy density and exhibiting high initial charge / discharge capacity and efficiency even under high voltage drive conditions.

[0063] [Equation 1]

[0064] Span = (D) 90 -D 10 ) / D 50

[0065] In equation 1, D10 D is the particle size of particles that have a cumulative volume of 10% in the particle size distribution. 50 It is the particle size of the particles that have a cumulative volume of 50% in the particle size distribution, and D 90 It is the particle size of particles that have a cumulative volume of 90% in the particle size distribution.

[0066] According to some embodiments, the average particle size (D) of the positive electrode active material 50 The average particle size can be from about 8 μm to about 25 μm, for example from about 9 μm to about 20 μm, or from about 10 μm to about 15 μm. The average particle size can be measured by methods known to those skilled in the art, such as by a particle size analyzer or by transmission electron microscopy or scanning electron microscopy images. Alternatively, the average particle size value can be obtained by measuring using dynamic light scattering, performing data analysis, counting the number of particles in each particle size range, and thereby calculating the average particle size. Here, the average particle size means the diameter (D) of the particles having a cumulative volume of 50% of the particle size distribution obtained by randomly measuring the size (diameter or major axis length) of about 20 particles in a scanning electron microscopy image of the positive electrode active material. 50 ).

[0067] D of the positive electrode active material 10 It can be about 1 μm to about 12 μm, for example about 2 μm to about 11 μm, about 3 μm to about 10 μm, about 4 μm to about 9 μm, or about 5 μm to about 8 μm. Here, D 10 The particle size distribution can be obtained by using a particle size analyzer, and the diameter of particles having a cumulative volume of 10% of the total volume in the particle size distribution can be used as D. 10 .

[0068] D of the positive electrode active material 90 It can be about 15 μm to about 25 μm, for example about 16 μm to about 24 μm, about 17 μm to about 23 μm, or about 18 μm to about 22 μm. Here, D 90 The particle size distribution can be obtained by using a particle size analyzer, and the diameter of the particles that account for 90% of the cumulative volume in the particle size distribution can be used as D. 90 .

[0069] When the D of the positive electrode active material 50 D 10 and D 90 Within the aforementioned range, the density of the positive electrode active material layer can be maximized, thereby increasing the capacity of the rechargeable lithium battery while improving energy density and cycle life characteristics.

[0070] Particle size analysis of the positive electrode active material can be performed using a particle size analyzer such as the LS13320 (Beckmann Coulter) employing laser diffraction. As part of the particle size analysis conditions, the pump speed can be 55%, ultrasonic dispersion can be performed at 40 kHz for 30 seconds, the run length can be 60 seconds, the refractive index can be 1.6, the e-factor (extinction factor) can be 1.00, the sample amount can be 0.20 g, and the dispersant added to the sample can be 1 ml of 10% sodium hexametaphosphate.

[0071] Methods for preparing positive electrode active materials

[0072] In some embodiments, the method for preparing the positive electrode active material includes: (i) preparing (preparing) core particles comprising a lithium nickel-based composite oxide; (ii) adding and mixing cobalt raw materials, aluminum raw materials and yttrium raw materials into an aqueous solvent to prepare a coating solution; (iii) adding and mixing the core particles into the coating solution to prepare a mixed solution; and (iv) removing the aqueous solvent from the mixed solution, and then drying and heat-treating the product to obtain the positive electrode active material.

[0073] In a method for preparing a positive electrode active material according to some embodiments, core particles comprising a lithium-nickel-based composite oxide can be prepared by mixing a nickel-based composite hydroxide and a lithium raw material and subjecting them to a first heat treatment. The nickel-based composite hydroxide can be a precursor of the core particles and can be in the form of secondary particles aggregated from primary particles. The nickel-based composite hydroxide can be prepared by a co-precipitation method.

[0074] In nickel-based composite hydroxides, the nickel content based on 100 mol% of total metal can be greater than or equal to about 80 mol%, for example, greater than or equal to about 82 mol%, greater than or equal to about 85 mol%, greater than or equal to about 87 mol%, greater than or equal to about 90 mol%, or greater than or equal to about 91 mol%, and can be less than or equal to about 99 mol%, for example, less than or equal to about 95 mol%. When the nickel content is within these ranges, high capacity can be achieved, which provides high-capacity, high-density rechargeable lithium batteries.

[0075] In nickel-based composite hydroxides, the cobalt content based on 100 mol% of total metal can be greater than or equal to about 1 mol%, for example, about 1 mol% to about 10 mol%, about 1 mol% to about 5 mol%, or about 1 mol% to about 3 mol%. When the cobalt content is within these ranges, particle damage during the compression process is effectively suppressed, accelerated particle degradation during charging and discharging is prevented, and a kinetic balance between lithium ions and electrons is formed, which has the advantage of improving the cycle life characteristics of rechargeable lithium batteries.

[0076] When the nickel-based composite hydroxide includes aluminum, the aluminum content may be greater than or equal to about 0.1 mol%, greater than or equal to about 0.5 mol%, or greater than or equal to about 1 mol%, for example, about 1 mol% to about 3 mol%, about 1 mol% to about 2.5 mol%, or about 1 mol% to about 2 mol%, based on 100 mol% of the total metals. When the aluminum content in the composite hydroxide is within these ranges, the structural stability of the positive electrode active material can be improved while providing high capacity, and the manufacturing cost can be reduced.

[0077] The nickel-based composite hydroxide may be represented by, for example, Chemical Formula 11.

[0078] [Chemical Formula 11]

[0079] Ni x11 M 11 y11 M 12 z11 (OH)2

[0080] In Chemical Formula 11, 0.3≤x11≤1, 0≤y11≤0.7, 0≤z11≤0.7, and 0.9≤x11+y11+z11≤1.1, M 11 and M 12 are different from each other and are each independently one or more selected from Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn, and Zr. In further embodiments of Chemical Formula 11, 0.6≤x11≤1, 0≤y11≤0.4 and 0≤z11≤0.4, or 0.8≤x11≤1, 0≤y11≤0.2 and 0≤z11≤0.2, or 0.9≤x11<1, 0<y11≤0.1 and 0≤z11≤0.1.

[0081] As a specific example, the nickel-based composite hydroxide may be represented by Chemical Formula 12 or Chemical Formula 13.

[0082] [Chemical Formula 12]

[0083] Ni x12 Co y12 M 13 z12 (OH)2

[0084] In Chemical Formula 12, 0.8≤x12<1, 0<y12≤0.2, 0≤z12≤0.2, and 0.9≤x12+y12+z12≤1.1, M 13It is one or more of Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn, and Zr. In a further embodiment of chemical formula 12, 0.9 ≤ x12 ≤ 0.99, 0.01 ≤ y12 ≤ 0.1, and 0 ≤ z12 ≤ 0.1.

[0085] [Chemical Formula 13]

[0086] Ni x13 Co y13 M 14 z13 M 15 w13 (OH)2

[0087] In chemical formula 13, 0.8 ≤ x13 ≤ 0.98, 0.01 ≤ y13 ≤ 0.19, 0.01 ≤ z13 ≤ 0.19, 0 ≤ w13 ≤ 0.19 and 0.9 ≤ x13 + y13 + z13 + w13 ≤ 1.1, M 14 It is one or more of Al and Mn, and M 15 It is one or more of B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn, and Zr. In a further embodiment of chemical formula 13, 0.9 ≤ x13 ≤ 0.98, 0.01 ≤ y13 ≤ 0.09, 0.01 ≤ z13 ≤ 0.09, and 0 ≤ w13 ≤ 0.09.

[0088] Nickel-based composite hydroxides can be in particulate form, and the average particle size (D) of the particles is... 50 The size can be approximately 10 μm to approximately 18 μm, approximately 11 μm to approximately 16 μm, or approximately 12 μm to approximately 15 μm.

[0089] The nickel-based composite hydroxide and the lithium raw material can be mixed at a molar ratio of metal in the nickel-based composite hydroxide to lithium in the lithium raw material of about 1:0.9 to about 1:1.8, for example at a molar ratio of metal in the nickel-based composite hydroxide to lithium in the lithium raw material of about 1:0.9 to about 1:1.5 or about 1:1 to about 1:1.2.

[0090] The first heat treatment may be carried out in an oxygen atmosphere and at a temperature range, for example, from about 650 °C to about 850 °C, from about 680 °C to about 800 °C, or from about 710 °C to about 750 °C. The first heat treatment may be carried out for about 2 hours to about 20 hours or from about 8 hours to about 15 hours.

[0091] Lithium-nickel-based composite oxides can be obtained through a first heat treatment. In these lithium-nickel-based composite oxides, based on 100 mol% of total metals excluding lithium, the nickel content can be greater than or equal to about 80 mol%, the cobalt content can be about 1 mol% to about 3 mol%, and the aluminum content can be about 1 mol% to about 3 mol%. Compared to oxides with other compositions, such as lithium-nickel-cobalt-manganese-based composite oxides or lithium-cobalt-based oxides, these composite oxides have significantly different amounts of residual lithium on the particle surface and different surface properties, making it difficult to form a good coating layer in the form of a uniform film using existing coating methods. The method according to embodiments of this disclosure simultaneously coats the particle surface of lithium-nickel-based composite oxides with cobalt, aluminum, and yttrium to a very uniform thickness.

[0092] In some embodiments, a coating solution is prepared by mixing cobalt raw materials, aluminum raw materials, and yttrium raw materials in an aqueous solvent. Core particles comprising a lithium-nickel-based composite oxide, obtained through a first heat treatment, are then added and mixed. Drying and a second heat treatment are then performed to form a coating layer according to some example embodiments. This is a salt-dissolving wet coating method and can be a pre-addition (first-addition) method in which the salt, as the coating raw material, is first completely dissolved, and then the active material particles are added.

[0093] Aqueous solvents may include distilled water, alcohol solvents, or combinations thereof. Aluminum raw materials may be, for example, aluminum sulfate, aluminum nitrate, aluminum acetate, or combinations thereof. Cobalt raw materials may be cobalt sulfate, cobalt nitrate, cobalt acetate, or combinations thereof, and yttrium raw materials may be yttrium sulfate, yttrium nitrate, yttrium acetate, or combinations thereof.

[0094] Based on a total of 100 mol% of metals other than lithium, cobalt from the cobalt raw material, aluminum from the aluminum raw material, and yttrium from the yttrium raw material in the core particles, the amount of cobalt in the cobalt raw material can be from about 0.1 mol% to about 5.0 mol%, for example, from about 0.5 mol% to about 4.0 mol%, from about 1.0 mol% to about 3.0 mol%, or from about 1.5 mol% to about 2.5 mol%. By providing cobalt coating content within these ranges, a coating layer with a thin and uniform thickness can be formed, and the storage and long cycle life characteristics of the battery including the positive electrode active material under high-temperature operating conditions can be improved.

[0095] Based on a total of 100 mol% of metals other than lithium, cobalt from cobalt raw materials, aluminum from aluminum raw materials, and yttrium from yttrium raw materials in the core particles, the amount of aluminum in the aluminum raw materials can be from about 0.1 mol% to about 3.5 mol%, for example from about 0.1 mol% to about 3.0 mol%, from about 0.2 mol% to about 2.5 mol%, from about 0.2 mol% to about 2.0 mol%, from about 0.3 mol% to about 1.5 mol%, from about 0.3 mol% to about 1.0 mol%, or from about 0.4 mol% to about 0.7 mol%. By providing aluminum coating amounts within these ranges, a coating layer with a thin and uniform thickness can be formed, and the storage and long cycle life characteristics of the battery including the positive electrode active material under high-temperature operating conditions can be improved.

[0096] Based on a total of 100 mol% of metals other than lithium, cobalt from cobalt raw materials, aluminum from aluminum raw materials, and yttrium from yttrium raw materials in the core particles, the amount of yttrium in the yttrium raw materials can be from about 0.1 mol% to about 0.5 mol%, for example, from about 0.1 mol% to about 0.4 mol%, from about 0.1 mol% to about 0.3 mol%, or from about 0.1 mol% to about 0.2 mol%. By providing yttrium coating content within these ranges, a coating layer with a thin and uniform thickness can be formed, and storage and long cycle life characteristics under high-temperature operating conditions can be improved.

[0097] The cobalt, aluminum, and yttrium raw materials can be mixed in an aqueous solvent for about 1 minute to about 60 minutes, for example, about 3 minutes to about 30 minutes, or about 5 minutes to about 10 minutes. Alternatively, mixing can be carried out at a mixing speed of about 100 rpm to about 800 rpm, for example, about 200 rpm to about 600 rpm, or about 250 rpm to about 500 rpm. Using these mixing conditions, the cobalt, aluminum, and yttrium raw materials can be completely dissolved in the aqueous solvent to prepare a colorless and transparent coating solution, which can be used to form a uniform coating layer. In some embodiments, the fully mixed coating solution may have a pH of about 1.5 to about 4, for example, about 2.0 to about 3.5, about 2.5 to about 3.3, about 2.7 to about 3.3, or about 2.9 to about 3.2.

[0098] The core particles are then added to the prepared coating solution. Adding the core particles while stirring the coating solution improves coating quality. The time for introducing the core particles into the coating solution can be approximately 30 seconds / 500g to approximately 2 minutes / 500g, for example, approximately 30 seconds / 500g to approximately 1.5 minutes / 500g. The core particles can be added at an appropriate rate to control the pH of the supernatant after coating, thereby effectively forming a uniform coating layer. If the rate of core particle addition is too slow, the reaction rate for each particle may vary, making it impossible to form a uniform coating layer. If the rate of core particle addition is too fast, the pH may change rapidly, which prevents the formation of a uniform coating layer.

[0099] After all the core particles are added to the coating solution, stirring can be performed for approximately 15 to approximately 60 minutes, for example, approximately 20 to approximately 50 minutes, or approximately 30 to approximately 45 minutes. The time from the start of adding the core particles to the completion of stirring (i.e., the coating reaction time) can be adjusted to approximately 1 hour.

[0100] In some embodiments, when the addition of core particles to the coating solution is stopped, i.e., when mixing or coating is complete, the supernatant may have a pH in the range of about 5.5 to about 8.5. If the pH of the supernatant is less than about 5.5, the acidity becomes too strong and a uniform coating layer may not be formed. If the pH is greater than about 8.5, the alkalinity becomes too strong, making it difficult to form a uniform coating layer.

[0101] After removing the aqueous solvent from the mixed solution, the obtained product can be dried, for example, under vacuum conditions at about 40 °C to about 240 °C, about 100 °C to about 220 °C, or about 150 °C to about 200 °C. Thus, satisfactory coated products can be obtained using these conditions.

[0102] The completely dried product after removing the aqueous solvent from the mixed solution can be referred to as the coated product. The coated product may include core particles and a coating layer formed on the surface of the core particles, wherein the coating layer includes cobalt, aluminum, and yttrium. The coating layer may be fibrous, mesh-like, or spiderweb-like in shape. Such a mesh can be continuously formed across (covering) the surface of the core particles. A mesh-shaped coating layer can wrap the core particles with a very thin and uniform thickness, thereby strengthening the surface of the positive electrode active material and improving structural stability. As a result, the high-temperature and high-voltage characteristics of the battery including the positive electrode active material can be improved.

[0103] The heat treatment described above after mixing the nickel-based composite hydroxide and the lithium raw material can be referred to as the first heat treatment, and the heat treatment of the coated product can be referred to as the second heat treatment. The second heat treatment can be a process (process) of forming a coating layer in an oxygen atmosphere at a temperature range of about 600 °C to about 850 °C, about 650 °C to about 800 °C, or about 700 °C to about 750 °C for about 2 hours to about 20 hours or about 3 hours to about 10 hours.

[0104] positive electrode

[0105] In some embodiments, the positive electrode includes a current collector and a layer of positive electrode active material on the current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material. In addition to the aforementioned positive electrode active material, the positive electrode active material layer may further include other types of positive electrode active materials. The positive electrode active material layer may further include a binder, a conductive material, or a combination thereof.

[0106] According to some embodiments, the positive electrode active material layer may have a content of approximately 10 mg / cm². 2 Approximately 40 mg / cm 2 For example, approximately 10 mg / cm 2 Approximately 30 mg / cm 2 or about 10 mg / cm 2 Approximately 20 mg / cm 2 The loading level. Additionally, in the final positive electrode obtained through compression, the positive electrode active material layer may have a density of approximately 3.3 g / cc to approximately 4.5 g / cc, for example, approximately 3.3 g / cc to approximately 4.0 g / cc, approximately 3.4 g / cc to approximately 4.2 g / cc, approximately 3.5 g / cc to approximately 3.85 g / cc, approximately 3.3 g / cc to approximately 3.85 g / cc, or approximately 3.4 g / cc to approximately 4.2 g / cc. Applying the positive electrode active material according to some example embodiments can advantageously achieve such a loading level and density of the positive electrode, and a positive electrode having such a range of loading levels and densities provides a rechargeable lithium battery with high capacity and high energy density.

[0107] The positive electrode active material layer can have a thickness of about 5 μm to about 200 μm, for example, about 5 μm to about 180 μm, or about 10 μm to about 150 μm. When the positive electrode active material layer has a thickness within the range described above, a battery with high capacity and high energy density can be provided.

[0108] adhesive

[0109] The binder is used to adhere the positive electrode active material particles to each other and also to adhere the positive electrode active material to the current collector. Examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers including ethylene oxide (including polymers of ethylene oxide), polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylate resin, polyester resin, nylon, etc. However, this disclosure is not limited to these examples.

[0110] conductive materials

[0111] Conductive materials are used to impart conductivity to electrodes and can be any material that conducts electrons without causing undesirable chemical changes in a battery. Examples of conductive materials include carbon-based materials such as natural graphite, synthetic graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metal-based materials containing copper, nickel, aluminum, silver, etc., in the form of metal powders or metal fibers; conductive polymers such as polyphenylene derivatives; or mixtures thereof.

[0112] Based on a 100% by weight positive electrode active material layer, the amounts of binder and conductive material can be from about 0.5% by weight to about 5% by weight, respectively.

[0113] The current collector can be formed from an aluminum thin film, but is not limited to this.

[0114] Rechargeable lithium batteries

[0115] Some embodiments provide a rechargeable lithium battery that includes the above-described positive electrode, negative electrode, and electrolyte. For example, a rechargeable lithium battery may include a positive electrode, a negative electrode, a separator between the positive and negative electrodes, and an electrolyte solution.

[0116] Depending on their shape, rechargeable lithium batteries can be cylindrical, prismatic, pouch-shaped, coin-shaped, etc. Figures 1 to 4 To illustrate a schematic diagram of a rechargeable lithium battery according to some embodiments, wherein Figure 1 It is a cylindrical battery. Figure 2 It is a prismatic battery, and Figure 3 and 4 It is a pouch-shaped battery. (See reference) Figures 1 to 4 The rechargeable lithium battery 100 includes an electrode assembly 40 and a housing 50. The electrode assembly 40 has a separator 30 between a positive electrode 10 and a negative electrode 20, and the electrode assembly 40 is housed within the housing 50. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte solution (not shown). The rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50, such as... Figure 1 As shown. Figure 2 As shown, the rechargeable lithium battery 100 may include a positive electrode lead connector 11, a positive electrode terminal 12, a negative electrode lead connector 21, and a negative electrode terminal 22. For example... Figure 3 and 4 As shown, the rechargeable lithium battery 100 may include electrode terminals 70, namely positive electrode terminal 71 and negative electrode terminal 72, which form an electrical path for leading the current formed in the electrode assembly 40 to the outside of the battery.

[0117] negative electrode

[0118] The negative electrode may include a current collector and a negative electrode active material layer on the current collector, and the negative electrode active material layer may include a negative electrode active material. The negative electrode active material layer may further include a binder, a conductive material, or a combination thereof.

[0119] Negative electrode active material

[0120] The negative electrode active material may include materials that can reversibly insert / deintercalate lithium ions, lithium metal, lithium metal alloys, materials that can be doped / dedoped with lithium, or transition metal oxides.

[0121] Materials that can reversibly insert / deintercalate lithium ions may include carbon-based negative electrode active materials, such as crystalline carbon, amorphous carbon, or combinations thereof. Crystalline carbon may be graphite, such as unshaped, flake, scaly, spherical, or fibrous natural or artificial graphite, and amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization products, calcined coke, etc.

[0122] Lithium metal alloys may include alloys of lithium and metals selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0123] Materials capable of doping / dedoping lithium can be Si-based or Sn-based negative electrode active materials. Si-based negative electrode active materials may include silicon, silicon-carbon composites, and SiO₂. x(0<x≤2), a Si-Q alloy, or a combination thereof. In the formula Si-Q, Q is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, such as Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof. The Sn-based negative electrode active material may be Sn, SnO₂, a Sn alloy, or a combination thereof.

[0124] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle diameter (D of the silicon-carbon composite particles 50 ) may be, for example, from about 0.5 μm to about 20 μm. According to some embodiments, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surfaces of the silicon particles. For example, the silicon-carbon composite may include secondary particles (core) in which silicon primary particles are aggregated, and an amorphous carbon coating layer (shell) on the surfaces of the secondary particles. Amorphous carbon may also be present between the silicon primary particles, for example, the silicon primary particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.

[0125] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include: a core comprising crystalline carbon and silicon particles, and an amorphous carbon coating layer on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include soft carbon or hard carbon, a mesophase pitch carbonized product, and calcined coke.

[0126] When the silicon-carbon composite includes silicon and amorphous carbon, based on 100 wt% of the silicon-carbon composite, the amount of silicon may be from about 10 wt% to about 50 wt%, and the amount of amorphous carbon may be from about 50 wt% to about 90 wt%. In addition, when the composite includes silicon, amorphous carbon, and crystalline carbon, based on 100 wt% of the silicon-carbon composite, the amount of silicon may be from about 10 wt% to about 50 wt%, the amount of crystalline carbon may be from about 10 wt% to about 70 wt%, and the amount of amorphous carbon may be from about 20 wt% to about 40 wt%.

[0127] The thickness of the amorphous carbon coating layer may be from about 5 nm to about 100 nm. The average particle diameter (D of the silicon particles (primary particles) 50 ) may be from about 10 nm to about 1 μm, or from about 10 nm to about 200 nm. The silicon particles may exist as elemental silicon, be in the form of a silicon alloy, or be in an oxidized form. The oxidized form of silicon may be represented by SiO x(0<x≤2). The atomic content ratio of Si:O indicating the oxidation degree may be about 99:1 to about 33:67. Here, the average particle diameter (D 50 ) represents the diameter of particles at a cumulative volume of about 50 vol% in the particle size distribution.

[0128] The Si-based negative electrode active material or Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. When the Si-based negative electrode active material or Sn-based negative electrode active material is mixed with the carbon-based negative electrode active material, the mixing ratio is a weight ratio of about 1:99 to about 90:10.

[0129] adhesive

[0130] The binder serves to attach the negative electrode active material particles to each other, and also serves to attach the negative electrode active material to the current collector. The binder may include a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.

[0131] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.

[0132] The aqueous binder may be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.

[0133] When an aqueous binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. The cellulose-based compound may include at least one of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or an alkali metal salt thereof. The alkali metal may include Na, K or Li.

[0134] The dry binder may be a polymer material capable of forming fibers. The dry binder may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.

[0135] conductive materials

[0136] This includes conductive materials to provide electrode conductivity, and any electrically conductive material that can be used in the battery without causing undesirable chemical changes. Examples of conductive materials include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, carbon nanotubes, etc.; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.

[0137] Based on 100% by weight of the negative electrode active material layer, the amount of negative electrode active material can be from about 95% by weight to about 99.5% by weight, and based on 100% by weight of the negative electrode active material layer, the amount of binder can be from about 0.5% by weight to about 5% by weight. For example, the negative electrode active material layer may include about 90% by weight to about 99% by weight of negative electrode active material, about 0.5% by weight to about 5% by weight of binder, and about 0.5% by weight to about 5% by weight of conductive material.

[0138] current collector

[0139] The current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or alloys thereof, and may be in the form of foil, sheet, or foam. The thickness of the current collector may be, for example, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 7 μm to about 10 μm.

[0140] electrolytes

[0141] The electrolyte used in rechargeable lithium batteries may be an electrolyte solution, which may include non-aqueous organic solvents and lithium salts.

[0142] Non-aqueous organic solvents are used as media for transporting ions that participate in the electrochemical reactions of a battery. Non-aqueous organic solvents can be carbonate (carbonate-based) solvents, ester (ester-based) solvents, ether (ether-based) solvents, ketone (ketone-based) solvents, alcohol (alcohol-based) solvents, aprotic solvents, or combinations thereof.

[0143] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and butyl carbonate (BC). Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, decanolactone, mevalonolactone, valproic acid lactone, and caprolactone. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, and tetrahydrofuran. Additionally, ketone solvents may include cyclohexanone. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles such as R-CN (where R is a C2 to C20 straight-chain, branched or cyclic hydrocarbon group, and may include double bonds, aromatic rings or ether groups, etc.); amides such as dimethylformamide; dioxolane such as 1,3-dioxolane, 1,4-dioxolane, etc.; sulfolane, etc.

[0144] Non-aqueous organic solvents can be used alone or in mixtures of two or more types. When two or more types are used in mixtures, the mixing ratio can be appropriately adjusted according to the desired battery performance, as is known to those skilled in the art.

[0145] When using carbonate solvents, cyclic carbonates and chain carbonates can be mixed and used together, and the cyclic carbonates and chain carbonates can be mixed in a volume ratio of about 1:1 to about 1:9.

[0146] Non-aqueous organic solvents may further include aromatic hydrocarbon organic solvents. For example, carbonate solvents and aromatic hydrocarbon organic solvents may be mixed and used in a volume ratio of about 1:1 to about 30:1.

[0147] The electrolyte solution may further include vinylene carbonate, vinylene carbonate, or ethylene carbonate compounds to improve battery cycle life.

[0148] Examples of ethylene carbonate compounds include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.

[0149] Lithium salts dissolved in organic solvents supply lithium ions in the battery, enabling basic operation of rechargeable lithium batteries and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts may include at least one of the following: LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO2C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2 (where x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate)borate (LiBOB).

[0150] The concentration of lithium salt can be in the range of about 0.1 M to about 2.0 M. If the concentration of lithium salt is within this range, the electrolyte solution has suitable ionic conductivity and viscosity, and therefore excellent performance can be achieved and lithium ions can move efficiently.

[0151] diaphragm

[0152] Depending on the type of rechargeable lithium battery, a separator may be present between the positive and negative electrodes. The separator may include multilayer films of polyethylene, polypropylene, polyvinylidene fluoride, or two or more layers thereof, and mixed multilayer films such as polyethylene / polypropylene two-layer separators, polyethylene / polypropylene / polyethylene three-layer separators, polypropylene / polyethylene / polypropylene three-layer separators, etc.

[0153] The diaphragm may include a porous substrate and a coating on one or both surfaces of the porous substrate, comprising organic materials, inorganic materials, or combinations thereof.

[0154] The porous substrate may be a polymer film formed from any of the following polymers: polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate and polybutylene terephthalate; polyacetal; polyamide; polyimide; polycarbonate; polyetherketone; polyaryletherketone; polyetherimide; polyamideimide; polybenzimidazole; polyethersulfone; polyphenylene ether; cyclic olefin copolymers; polyphenylene sulfide; polyethylene naphthalate; Teflon®; and polytetrafluoroethylene; or copolymers or mixtures thereof. The porous substrate may include glass fiber, or may include a composite film of polymer and glass fiber.

[0155] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.

[0156] Organic materials may include (meth)acrylic acid copolymers, which include a first structural unit and a second structural unit derived from (meth)acrylamide, the second structural unit including at least one structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acryloylaminosulfonic acid or a salt thereof.

[0157] Inorganic materials may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof, but this disclosure is not limited to these examples. The average particle size (D) of the inorganic particles... 50 The wavelength can be from about 1 nm to about 2000 nm, for example from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.

[0158] Organic and inorganic materials can be mixed in a single coating. In another embodiment, a coating comprising organic materials and a coating comprising inorganic materials can be stacked.

[0159] The coating thickness can be from about 0.5 μm to about 20 μm, for example from about 1 μm to about 10 μm or from about 1 μm to about 5 μm.

[0160] The following describes embodiments and comparative examples of the present disclosure. However, the present disclosure is not limited to the following embodiments.

[0161] Example 1

[0162] 1. Preparation of positive electrode active material

[0163] Make Ni 0.965 Co 0.02 Al 0.015 (OH)₂ and LiOH were mixed in a molar ratio of 1:1.03, and then subjected to a first heat treatment at 730 °C for 13 hours under an oxygen atmosphere to prepare particles with an average size (D) of approximately 12 μm. 50 The secondary particles of Li 1.03 Ni 0.965 Co 0.02 Al 0.015 The composition of O2 is a lithium nickel-based composite oxide.

[0164] In a 1 L reactor, the coating solution was prepared as follows: 600 g of distilled water, cobalt sulfate, aluminum sulfate, and yttrium sulfate were added, and the mixture was stirred at approximately 350 rpm for about 5 minutes to dissolve the salts. The coating solution, in which the salts were completely dissolved, was confirmed to be colorless and transparent. While continuously stirring the coating solution, 500 g of lithium-nickel-based composite oxide was added for 1.5 minutes. Stirring was then continued for 30 minutes. Based on 100 mol% of the total metals other than lithium in the final positive electrode active material, cobalt sulfate had a cobalt content of 2.0 mol%, aluminum sulfate had an aluminum content of 0.5 mol%, and yttrium sulfate had a yttrium content of 0.1 mol%.

[0165] After removing the solvent from the mixed solution using a suction device and a filter press, the coated product was obtained by vacuum drying at 190 °C.

[0166] The coated product is subjected to a second heat treatment at 710 °C for 10 hours in an oxygen atmosphere to obtain the final positive electrode active material.

[0167] 2. Manufacturing of rechargeable lithium battery cells

[0168] A slurry for the positive electrode active material layer was prepared by mixing 98.5 wt% of the positive electrode active material, 1.0 wt% of polyvinylidene fluoride binder, and 0.5 wt% of carbon nanotube conductive material in N-methyl-2-pyrrolidone (NMP) solvent. The slurry was coated onto an aluminum foil current collector, then dried and compressed to form the positive electrode. The positive electrode active material layer had a strength of 20 mg / cm³. 2 The loading level, and the final positive electrode obtained by compression has a density of about 3.4 g / cc.

[0169] A negative electrode active material slurry was prepared by mixing 97.5 wt% graphite negative electrode active material, 1.5 wt% carboxymethyl cellulose, and 1 wt% styrene-butadiene rubber in an aqueous solvent. The negative electrode active material slurry was coated onto a copper foil current collector, dried, and pressed to form a negative electrode.

[0170] The positive and negative electrodes are used together with a polytetrafluoroethylene membrane and an electrolyte solution to produce a rechargeable lithium battery cell according to conventional methods. The electrolyte solution is prepared by mixing ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7 and dissolving 1 M LiPF6 in the mixed solvent.

[0171] Example 2

[0172] The positive electrode active material and rechargeable lithium battery cell were prepared in the same manner as in Example 1, except that: based on 100 mol% of the total metals other than lithium in the final positive electrode active material, yttrium sulfate has a yttrium content of 0.2 mol%.

[0173] Comparative Example 1

[0174] The positive electrode active material and rechargeable lithium battery cell were prepared in the same manner as in Example 1, except that the positive electrode active material was prepared by performing a cobalt coating process without aluminum and yttrium coating processes (i.e., without adding aluminum sulfate and yttrium sulfate to the lithium nickel-based composite oxide of Example 1).

[0175] Comparative Example 2

[0176] The positive electrode active material and the rechargeable lithium battery cell were prepared in the same manner as in Comparative Example 1, except that the cobalt content of cobalt sulfate was designed to be 3.0 mol% based on 100 mol% of the total metals other than lithium in the final positive electrode active material.

[0177] Comparative Example 3

[0178] The positive electrode active material and rechargeable lithium battery cell were prepared in the same manner as in Example 1, except that the positive electrode active material was prepared by performing a separate aluminum coating process without the cobalt and yttrium coating process (i.e., without adding cobalt sulfate and yttrium sulfate to the lithium nickel-based composite oxide of Example 1).

[0179] Comparative Example 4

[0180] The positive electrode active material and the rechargeable lithium battery cell were prepared in the same manner as in Comparative Example 3, except that the aluminum content of aluminum sulfate was designed to be 1.0 mol based on 100 mol% of the total metals other than lithium in the final positive electrode active material.

[0181] Comparative Example 5

[0182] The positive electrode active material and rechargeable lithium battery cell were prepared in the same manner as in Example 1, except that the positive electrode active material was prepared by performing separate cobalt and aluminum coating processes without yttrium coating processes (i.e., without adding yttrium sulfate to the lithium nickel-based composite oxide of Example 1).

[0183] Comparative Example 6

[0184] The positive electrode active material and the rechargeable lithium battery cell were prepared in the same manner as in Comparative Example 5, except that: based on 100 mol% of the total metals other than lithium in the final positive electrode active material, the cobalt content of cobalt sulfate was 3.0 mol%, and based on 100 mol% of the total metals other than lithium in the final positive electrode active material, the aluminum content of aluminum sulfate was 1.0 mol%.

[0185] Evaluation 1: Surface and cross-sectional analysis of the active material of the positive electrode

[0186] The positive electrode active materials of Example 2 were compared with those of Comparative Examples 1, 4 and 6 by using images captured by scanning electron microscopy (SEM). Figure 5 These are SEM images of the surface of the positive electrode active material prepared in Example 2. Figure 6 These are SEM images of the surface of the positive electrode active material prepared in Comparative Example 1. Figure 7 These are SEM images of the surface of the positive electrode active material prepared in Comparative Example 4, and Figure 8 This is a SEM image of the surface of the positive electrode active material prepared in Comparative Example 6.

[0187] Reference Figures 6 to 8 This confirmed the formation of a cobalt and / or aluminum cladding layer on the surface of the core particles. However, as... Figure 5 As shown, aluminum and cobalt coatings, as well as yttrium coatings, are formed on the surface of the core particles.

[0188] The positive electrode active material of Example 2 was then compared by image acquisition using SEM-EDS (scanning electron microscopy-energy dispersive X-ray spectroscopy). SEM-EDS analysis was performed using a Helios G4HX manufactured by Thermo Fisher Scientific Inc. at 3 kV and 0.8 nA. Figure 9 This is a SEM-EDS image of yttrium in the coating layer on the surface of the positive electrode active material prepared in Example 2, and Figure 10 This is a SEM-EDS image of yttrium in the coating layer when observing the cross-section of the positive electrode active material prepared in Example 2.

[0189] refer to Figure 9 and 10 This confirms that yttrium is included in the coating layer on the surface of the core particles, specifically distributed in an island shape within the coating layer.

[0190] Evaluation 2: Analysis of the cobalt, aluminum, and yttrium content on the surface of the positive electrode active material

[0191] The content of cobalt, aluminum, and yttrium on the surface of the positive electrode active material was analyzed by SEM-EDS. SEM-EDS analysis was performed using a Helios G4 HX manufactured by Thermo Fisher Scientific Inc. at 3 kV and 0.8 nA.

[0192] Evaluation 3: Initial charge / discharge capacity and efficiency

[0193] The rechargeable lithium-ion battery cells according to the embodiments and comparative examples were charged at 25 °C with a constant current of 0.2 C to an upper limit voltage of 4.3 V and then charged with a constant voltage to 0.05 C, and then discharged at 0.2 C to a cutoff voltage of 3.0 V for initial charge and discharge. Table 1 below shows the initial charge capacity, initial discharge capacity, and the ratio of the latter to the former as efficiency.

[0194] Evaluation 4: High-temperature cycle life

[0195] After the initial charge and discharge of Evaluation 3, the battery cells were charged and discharged at 1.0 C for 50 or more cycles at 45 °C within a voltage range of 3.0 V to 4.4 V to calculate the ratio of the discharge capacity at the 50th cycle to the initial discharge capacity. The results are presented as high-temperature cycle life in Table 1.

[0196] Rating 5: High-temperature storage

[0197] After the initial charge and discharge of Evaluation 3, the battery cells were charged at 0.2 C to a voltage of 4.3 V, then stored at a high temperature of 75 °C for 14 days, and discharged at 0.2 C to a voltage of 3.0 V to measure the discharge capacity, and the ratio of the discharge capacity to the initial discharge capacity was calculated, which is provided as high temperature storage in Table 1.

[0198] Table 1

[0199]

[0200] Referring to Table 1, it can be seen that Examples 1 and 2 provide high initial charge / discharge capacity and initial charge / discharge efficiency, as well as excellent high-temperature cycle life and high-temperature storage characteristics.

[0201] On the other hand, Comparative Examples 1 and 2, which do not include aluminum and yttrium in the coating layer, exhibited poor high-temperature cycle life and high-temperature storage characteristics. Comparative Examples 3 and 4, which do not include cobalt and yttrium in the coating layer, exhibited poor initial discharge capacity, initial charge / discharge efficiency, high-temperature cycle life, and high-temperature storage characteristics. Comparative Examples 5 and 6, which do not include yttrium in the coating layer, exhibited poor high-temperature cycle life and high-temperature storage characteristics.

[0202] While this disclosure has been described with respect to exemplary embodiments that are now considered practical, it will be understood that this disclosure is not limited to the disclosed embodiments. Rather, this disclosure includes various modifications and equivalent arrangements.

Claims

1. Positive electrode active material, including: The core particles are in the form of secondary particles formed by the aggregation of primary particles, and the core particles comprise lithium nickel-based composite oxides. and A coating layer comprising cobalt, aluminum, and yttrium is disposed on the surface of the core particle.

2. The positive electrode active material according to claim 1, wherein, Based on 100 mol% of the total metals other than lithium in the positive electrode active material, the lithium-nickel-based composite oxide has a nickel content of greater than or equal to 80 mol%.

3. The positive electrode active material according to claim 1, wherein the lithium-nickel-based composite oxide further comprises aluminum, and in, The aluminum content is 1 mol% to 3 mol% based on 100 mol% of the total metals other than lithium in the lithium-nickel-based composite oxide.

4. The positive electrode active material according to claim 1, wherein the lithium-nickel-based composite oxide is represented by the following: Li a1 Ni x1 M 1 y1 M 2 z1 O 2-b1 X b1 Where 0.9≤a1≤1.8, 0.3≤x1≤1, 0≤y1≤0.7, 0≤z1≤0.7, 0.9≤x1+y1+z1≤1.1, 0≤b1≤0.1, M 1 and M 2 The elements are different and each is one or more of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn, and Zr, and X is one or more of F, P, and S.

5. The positive electrode active material according to claim 1, wherein, Based on 100 mol% of the total metals other than lithium in the positive electrode active material, the cobalt content in the coating layer is from 0.1 mol% to 5.0 mol%.

6. The positive electrode active material according to claim 1, wherein, Based on 100 mol% of the total metals other than lithium in the positive electrode active material, the aluminum content in the coating layer is from 0.1 mol% to 3.5 mol%.

7. The positive electrode active material according to claim 1, wherein, Based on 100 mol% of the total metals other than lithium in the positive electrode active material, the yttrium content in the coating layer is from 0.1 mol% to 0.5 mol%.

8. The positive electrode active material according to claim 1, wherein, Based on 100 mol% of the total metals other than lithium in the positive electrode active material, the ratio of cobalt content to aluminum content in the positive electrode active material is 1.5 to 2.

9. The positive electrode active material according to claim 1, wherein the positive electrode active material further comprises a grain boundary coating portion on the surface of the primary particle in the inner portion of the secondary particle, wherein the grain boundary coating portion comprises cobalt and aluminum.

10. The positive electrode active material according to claim 1, wherein the yttrium is in the coating layer in the form of islands.

11. The positive electrode active material according to claim 1, wherein the average particle size D of the positive electrode active material is... 50 The thickness ranges from 8 μm to 25 μm.

12. The positive electrode active material according to claim 1, wherein the positive electrode active material has a range of values ​​from 0.9 to 1.2 according to the following equation: Span = (D) 90 -D 10 ) / D 50 in, D 10 D is the particle size of particles that have a cumulative volume of 10% in the particle size distribution. 50 It is the particle size of particles that have a cumulative volume of 50% in the particle size distribution, and D 90 It is the particle size of particles that have a cumulative volume of 90% in the particle size distribution.

13. The positive electrode active material according to claim 1, wherein the thickness of the coating layer is from 5 nm to 200 nm.

14. Positive electrode, including: current collector; and The positive electrode active material layer on the current collector, The positive electrode active material layer thereunder comprises the positive electrode active material according to any one of claims 1 to 13.

15. The positive electrode according to claim 14, wherein the loading level of the positive electrode active material layer is 10 mg / cm³. 2 Up to 40 mg / cm 2 .

16. The positive electrode according to claim 14, wherein the density of the positive electrode active material layer is from 3.3 g / cc to 3.9 g / cc.

17. A rechargeable lithium battery, comprising: The positive electrode according to any one of claims 14 to 16; negative electrode; and Electrolytes.